Coming to terms with loss : explaining how people with amyotrophic lateral sclerosis engage with healthcare services - Foley, Geraldine (Trinity College (Dublin, Ireland). School of Social Work and Social Policy, 2014)
Amyotrophic lateral sclerosis (ALS), also known as motor neurone disease (MND), is a rapidly progressive and terminal neurological condition. ALS is a highly disabling condition and people with ALS ordinarily engage with healthcare services from symptom onset to end-of-life care. Researchers have already undertaken studies on perceptions and experiences of healthcare services among people with ALS but little was known about how and why people with ALS engage with healthcare services. The overarching aim of the study was to identify key parameters of healthcare experiences among people with ALS and to develop a substantive framework that explains how and why people with ALS engage with healthcare services.
Keywords: Social Work and Social Policy, Ph.D.; Ph.D. Trinity College Dublin